Participant Perspectives of Cognitive Rehabilitation for Type 2 Diabetes: Expectations and Impact. (19th August 2018) - Cuevas, Heather E.; Stuifbergen, Alexa K.; Ward, Catherine
Abstract : Purpose . To describe the experiences of people with type 2 diabetes who have completed a comprehensive cognitive rehabilitation intervention. Method . Nineteen participants with type 2 diabetes enrolled in an 8-week intervention consisting of 4 educational classes to learn strategies to improve cognitive function and an online training program at home to practice cognitively stimulating activities. Two focus groups were conducted as part of a study designed to assess the feasibility of the comprehensive cognitive rehabilitation intervention. Results . Three main themes were identified in the qualitative data: (1) expectations of cognitive change; (2) use of cognitive strategies; and (3) effect on diabetes self-management. Participants shared valuable insight into how their experiences with the intervention changed and how they viewed diabetes. Conclusions . While the participants did not initially tie their cognitive complaints to diabetes, they were able to show how and why they might use cognitive strategies to improve diabetes self-management activities. By adapting those strategies for diabetes, quality of life can improve as well as potentially glycemic control.